Eliminating cows' milk, but not wheat, barley or rye, increases the risk of growth deceleration and nutritional inadequacies. (25th April 2017) - Tuokkola, Jetta; Luukkainen, Päivi; Nevalainen, Jaakko; Ahonen, Suvi; Toppari, Jorma; Ilonen, Jorma; Veijola, Riitta; Knip, Mikael; Virtanen, Suvi M.; Kaila, Minna
Abstract: Aim: Our study examined the growth and nutritional intake of children on milk and/or wheat, barley or rye elimination diets. Methods: This was a nested case–control study within the Finnish Type 1 Diabetes Prediction and Prevention Study. It investigated 295 children born in the Tampere University Hospital area between 1997 and 2004 on a diet without cows' milk and/or wheat, barley or rye due to food allergies and 265 matched controls. Nutritional intake was recorded with three‐day food records at the ages of one, two and three years. Serial growth measurements were recorded annually up to the age of five years. Results: Despite consuming a balanced diet with sufficient energy and protein, the children on milk elimination diets grew slower than the control children (p = 0.009). Wheat, barley or rye elimination was not associated with growth. The intakes of protein and calcium were lower in children in the milk elimination group than the controls, at p < 0.05 for all. However, children on elimination diets consumed less saturated fats and sugar and more vitamin C and iron than the control children. Conclusion: Children on elimination diets faced an increased risk of growth deceleration and suboptimal intake of several micronutrients.